A preliminary note on population structure in eastern South Pacific common bottlenose dolphins, Tursiops truncatus - Sanino , G. Paolo; Waerebeek , Koen Van; Bressem , Marie-Francoise Van; Pastene , Luis A. (J. Cetacean Res. Manage., 2023)
Previous studies of eastern South Pacific common bottlenose dolphins, Tursiops truncatus, defined offshore and inshore ecotypes in Peru based on cranial and tooth morphology, documented the presence of a single resident inshore community (‘pod-R’) in central-north Chile, and confirmed the presence of offshore bottlenose dolphins off Chile. Here, mtDNA control region (331bp) was examined to evaluate genetic relationships between four geographic areas: inshore pod-R (n=8), Chilean offshore population (n=8), Peruvian inshore (n=3) and offshore (n=12) ecotypes. This is the first genetic analysis of T. truncatus in this ocean basin. Phylogenetic analysis grouped the three Peruvian specimens morphologically identified as inshore ecotype in an independent cluster, supported by 100% bootstrap value. The net genetic distance between Peruvian inshore and Peruvian offshore ecotypes was estimated at 2.9%, and even higher when compared with Chilean bottlenose dolphins. Morphological and mtDNA evidence combined argues for considering inshore and offshore ecotypes as evolutionary significant units, to be managed accordingly. Despite its inshore behavioural ecology, pod-R presented a high divergence from the Peruvian inshore ecotype and a relatively closer affinity with the Chilean offshore stock (3.41% and 0.87% net interpopulational distance, respectively). However, homogeneity tests showed significant genetic differences of pod-R with all other groups, including Chilean offshore. This, combined with a low nucleotide diversity (0.0069) and behavioural observations, suggest that pod-R may be reproductively isolated and active protection measures are recommended. Only one haplotype from a total of 21 was shared by Peruvian and Chilean offshore animals. Their net genetic distance was estimated at 0.024 and no significant differences were found in haplotype frequencies, suggesting a single, wide-ranging ‘Peru-Chile offshore stock’.